Consumer protection in financial institutions - Suwinto Johan; Ariawan Ariawan (Faculty of Law, University of Muhammadiyah Malang, 2021)
The relationship between financial institutions and customers is like two sides of a coin. On one hand, it is mutually beneficial, but on the other hand, this relationship can lead to mutual harm. Customers of financial institutions have a medium for a long-term relationships. Consumers of financial institutions generally have an average relationship of 24 months. Consumers make loan payments according to the agreed time. Customers will be able to get the right to the collateral if the loan has been paid. Conversely, if customers are unable to pay the installments on time, financial institutions will repose the collateral. From the inception of the loan to the repayment of the loan, the relationship between customers and financial institutions experiences several conditions. This research uses a normative judicial method, aiming to analyze consumer protection of non-bank financial institutions based on the existing laws and regulations. This research will focus on consumer protection from the start of the standard agreement, the fees or expenses charged, to the loan repayment mechanism. This research concludes that the protection of consumers of non-bank finance companies, especially finance companies, is still very weak. Consumer protection for finance companies, especially non-banks, has not been fully accommodated in the existing Consumer Protection Law. Therefore, the authority needs to issue a regulation in protecting the consumer in the financial industry.